2016
DOI: 10.15343/0104-7809.20164003362371
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de biscoitos diet adicionados de farinha da casca do maracujá avaliados sensorialmente por diabéticos

Abstract: O objetivo deste trabalho foi elaborar biscoitos diet adicionados de farinha da casca do maracujá para avaliação físico-química, microbiológica e sensorial por portadores de diabetes. Foram formulados três tipos de biscoitos: um controle sem farinha da casca de maracujá (B1) e dois experimentais adicionados, respectivamente de 7 % (B2) e 10 % (B3) de farinha da casca de maracujá. Inicialmente foram realizadas análises físico-químicas e microbiológicas. O teste sensorial foi realizado por 87 portadores de diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Cookies with low moisture content have a better shelf-life. Santiago, Silva, Conceição, and Aquino (2016) obtained higher moisture levels in diet cookies added with passion fruit peel flour, with values ranging from 9.35% to 11.54%. Uchoa et al (2009) reported that cookies supplemented with cashew powder presented a moisture content of 4.9%, and those containing guava power showed 4.1%, levels, which are lower than those reported in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Cookies with low moisture content have a better shelf-life. Santiago, Silva, Conceição, and Aquino (2016) obtained higher moisture levels in diet cookies added with passion fruit peel flour, with values ranging from 9.35% to 11.54%. Uchoa et al (2009) reported that cookies supplemented with cashew powder presented a moisture content of 4.9%, and those containing guava power showed 4.1%, levels, which are lower than those reported in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Diante desse resultado, os autores chegaram à conclusão que os produtos desenvolvidos com farinha da casca de maracujá podem auxiliar no tratamento de diabetes, principalmente por conta da maior concentração de fibras. Santiago et al (2016) realizaram a análise sensorial com uma amostragem de diabéticos, com faixa etária acima de 55 anos. Os biscoitos diet apresentaram boa aceitação sensorial, não havendo diferença estatística para nenhum dos atributos sensoriais avaliados.…”
Section: Resultsunclassified